Severe insulin resistance and intrauterine growth deficiency associated with haploinsufficiency for INSR and CHN2: new insights into synergistic pathways involved in growth and metabolism. - Suliman, S; Stanik, J; McCulloch, L; Wilson, N; Edghill, E; Misovicova, N; Gasperikova, D; Sandrikova, V; Elliott, K; Barak, L; Ellard, S; Volpi, E; et al. (2009)
OBJECTIVE: Digenic causes of human disease are rarely reported. Insulin via its receptor, which is encoded by INSR, plays a key role in both metabolic and growth signaling pathways. Heterozygous INSR mutations are the most common cause of monogenic insulin resistance. However, growth retardation is only reported with homozygous or compound heterozygous mutations. We describe a novel translocation [t(7,19)(p15.2;p13.2)] cosegregating with insulin resistance and pre- and postnatal growth deficiency. Chromosome translocations present a unique opportunity to identify modifying loci; therefore, our objective was to determine the mutational mechanism resulting in this complex phenotype. RESEARCH DESIGN AND METHODS: Breakpoint mapping was performed by fluorescence in situ hybridization (FISH) on patient chromosomes. Sequencing and gene expression studies of disrupted and adjacent genes were performed on patient-derived tissues. RESULTS Affected individuals had increased insulin, C-peptide, insulin-to-C-peptide ratio, and adiponectin levels consistent with an insulin receptoropathy. FISH mapping established that the translocation breakpoints disrupt INSR on chromosome 19p15.2 and CHN2 on chromosome 7p13.2. Sequencing demonstrated INSR haploinsufficiency accounting for elevated insulin levels and dysglycemia. CHN2 encoding beta-2 chimerin was shown to be expressed in insulin-sensitive tissues, and its disruption was shown to result in decreased gene expression in patient-derived adipose tissue. CONCLUSIONS: We present a likely digenic cause of insulin resistance and growth deficiency resulting from the combined heterozygous disruption of INSR and CHN2, implicating CHN2 for the first time as a key element of proximal insulin signaling in vivo.